Intravenous immunoglobulins may prevent prednisone-exacerbation in myasthenia gravis - Laura Díez-Porras (Nature Portfolio, 2020)
Abstract Corticosteroids may produce a paradoxical worsening of myasthenia gravis (MG) symptoms within the first weeks of treatment. We therefore wanted to assess the hypothesis that a prior infusion of intravenous immunoglobulin (IVIG) may have a protective effect. Our primary objectives were to show that the coadministration of immunoglobulins and glucocorticoids is safe and effective for controlling myasthenic symptoms, and to compare the exacerbation rate with this approach and historical practice without IVIG. We recruited 45 patients with generalized MG who required corticosteroids for the first time and we gave all IVIG before starting the full doses of prednisone. Monitoring was performed with validated scales, questionnaires, and blood tests over a 6-week period. Only 4.4% had severe adverse effects related to IVIG and 86.7% improved clinically. Notably, only 2.2% had a paradoxical symptom exacerbation in the first weeks of starting prednisone, which was statistically lower than the 42% reported in a historical series. We conclude that adjuvant therapy with IVIG when starting prednisone for the first time in patients with generalized MG is safe and effective. Given that the rate of paradoxical worsening was lower than that previously reported, the addition of IVIG may have a protective effect against such exacerbations.